2017
DOI: 10.1248/bpb.b17-00077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Inhibitory Effects of Metformin and Atorvastatin in Combination on Prostate Cancer Cells <i>in Vitro</i> and <i>in Vivo</i>

Abstract: Metformin is a commonly used drug for the treatment of type II diabetes and atorvastatin is the most prescribed cholesterol-lowering statin. The present study investigated the effects and mechanisms of metformin and atorvastatin in combination on human prostate cancer cells cultured in vitro and grown as xenograft tumor in vivo. Metformin in combination with atorvastatin had stronger effects on growth inhibition and apoptosis in PC-3 cells than either drug alone. The combination also potently inhibited cell mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…For, instance metformin in combination with imatinib was found to effective against colorectal cancer [ 13 ]. Similarly, metformin in combination with atorvastatin was found to be effective against prostate cancer [ 14 ]. There have been several reports on the effectiveness of metformin on ovarian cancer cells as well [ 15 17 ], but the direct target of this drug in ovarian cancer is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…For, instance metformin in combination with imatinib was found to effective against colorectal cancer [ 13 ]. Similarly, metformin in combination with atorvastatin was found to be effective against prostate cancer [ 14 ]. There have been several reports on the effectiveness of metformin on ovarian cancer cells as well [ 15 17 ], but the direct target of this drug in ovarian cancer is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed that Bcl-2 interacted with MSH2 in both PCa cells and tumor tissues of xenograft tumor mice. These results suggest that the anti-tumor effects of atorvastatin are correlated with DNA repair process of the tumor cells, which have never been reported in the previous studies [ 24 , 25 ]. These findings hint that the drugs might also play the anti-tumor effects on tumor cells through targeting the DNA repair associated molecules.…”
Section: Discussionsupporting
confidence: 57%
“…[ 49 ]). Indeed, metformin can potentiate the growth inhibitory effect of statins on tumor cell lines and the growth of primary tumors in nude mice [ 50 52 ]. Future studies will test potential synergy between statins and metformin (and related compounds) at inhibiting primary tumor growth and metastatic outgrowth in murine tumor models.…”
Section: Discussionmentioning
confidence: 99%